PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Gazali Gazali; Ummi Wahyuni (Assyarikah: Journal of Islamic Economic Business, 2021)
The  results  of  the  company's  work  will  depend  on  the  results  of  the performance of its employees. The company will try to improve the performance of its employees by encouraging its employees to work optimally with one way, namely  the  provision of  compensation.  This  is  in  accordance  with  the  theory which  says  that  satisfaction  with  compensation  can  affect  employee  behavior  to work more enthusiastically and spur high performance. This  research  is  classified  as  explanatory  research  with  a  quantitative approach.  The  sample  used  was  64  respondents  with  saturated  sampling technique. The type of data used is primary data, namely collecting data using a questionnaire.  The  data  analysis  used  is  Multiple  Linear  Regression  with  SPSS version 21 tool. The  results  of  this  study  indicate  that  compensation  is  able  to  have  a positive  impact  on  employee  performance,  with  a  significance  value  of  0.000 which  means  below  0.05  and  has  a  positive  coefficient  value  of  0.698.  Job satisfaction  is  able  to  have  a  positive  impact  on  employee  performance,  with  a significance  value  of  0.000  which  means  below  0.05  and  has  a  positive coefficient value of 0.522. Compensation is able to have a positive impact on job satisfaction, with a significance value of 0.000 which means below 0.05 and has a positive coefficient value of 1.334. and Compensation has a positive effect on employee  performance  with  Job  Satisfaction  as  an intervening  variable,  with  a significance value of 0.000 which means below 0.05 and has a calculated F value of 5486.521 which means above F table is 2.36.